Development of Snakes and Ladders Learning Media with The Teams Games Tournament Model to Improve Elementary Students’ Numeracy Skills - Devy Istofia Al Ubaidah; Triyanto Triyanto; Isnandar Slamet (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aimed to develop and evaluate the feasibility and effectiveness of Snakes and Ladders numeracy learning media integrated with the Teams Games Tournament (TGT) model for elementary geometry learning. Applying a research and development strategy along with the ADDIE model, the study included fifth-grade pupils who were split into two groups: one for experimental purposes and another as a control. Information was gathered through expert validation sheets, surveys for both students and teachers, and numeracy pretest–posttest instruments. The results of the validation indicated that the media was very valid, with scores of 92.3% and 93.8% from material experts, 91.3% from media experts, and 91.3% from practitioners. Practicality analysis indicated positive responses from students (82.92%) and teachers (96.7%), confirming the media was highly practical. Effectiveness analysis using the Independent Samples t- test revealed a significant difference in learning outcomes (Sig. 1-tailed = 0.000002 < 0.05. These results demonstrate that the Snakes and Ladders numeracy media integrated with the TGT model is feasible, practical, and effective in enhancing elementary students’ numeracy skills, providing better learning outcomes than conventional instruction.